Estudio de la prefabricación en concreto reforzado y su influencia en la construcción de estructuras en Colombia (2015)
The technique of prefabrication has existed for many years, improving with the passage of time as the concrete is also perfected. For the advancement of this technique, associations have arisen dedicated to the study, diffusion, research and development of the prefabricated concrete throughout the world. In Europe there is the "Federation Internationale de la Precontrainte (FIP)", the "Prestressed Concrete Development Group (PCDG)" and for America, in the United States there is the "Prestressed / Precast Concrete Institute (PCI)", as some main exponents. The prefabrication uses one of the most useful and versatile materials that man has to mold his environment. Since its application in ancient Rome, concrete has shown us iconic structures that never cease to amaze both designers and builders. Concrete and specifically pre-stressed and prefabricated concrete has been used since the beginning of the 20th century in Europe. Only until the middle of the last century, the techniques of prefabrication of concrete and pre-stressed concrete became an important influence for the construction industry as those developed mainly in the United States. At present, the prefabrication of concrete represents an industry that is synonymous with efficiency, quality, development and sustainability in the countries that have adopted and implemented it.